Folhetarias, poetas resistentes e cordel biográfico - Silva, Paulo Gracino da (2019)
This thesis presents a study about the Brazilian ―cordel‖ historiography, addressing the booklets and printed matter, publishers, poets, readers/listeners and sales methods, aiming to apprehend the resistance of the subjects that assisted to bring this type of literature to the classroom. In order to analyse those aforementioned elements, we used as a main reference the booklet Dom Helder, o profeta da paz, which was written by Medeiros Braga, a north-eastern ―cordelista‖. Analyzing the historical past and the miscellaneous interests that allowed the flourishing, the decline and the renovation of the traditional fair booklets, we saw in the surroundings of the 70s‘ and 80s‘ the essential context to identify the aspects that transformed its production in the country, concurring with the period of its great crisis and with the first steps towards the Brazilian educational system. Certeau (1982) and Farge (2011) grounded a dialogue between the writing and the possible places to History, whereas Burke (2008), Canclini (2015) and Chartier (2002a, 2003, 2004) fostered discussions about the concepts of culture, hybridization, interaction, appropriation and representation. With the specific historiography‘s assistance, those concepts are crucial to comprehend that the ―cordel‖ (as any culture) is reconstructed according to the social transformations and the inventive capacity of its agents. Herewith, we have seen that the poet resists remaining as a ―cordelista‖ and denounces the injustices of his world to survive whilst as a societal individual. As an example of a poet and poetry of resistance, Medeiros Braga presents in the 21st century the biographical booklet of Dom Hélder Câmara - a symbol of resistance in the struggle for peace and human rights during the Military Regime (1964-1985) - as a contribution to the process of political awareness of society.